Cutaneous squamous cell carcinoma of the head and neck with parotid gland metastasis mimicking mucoepidermoid carcinoma: a potential diagnostic pitfall - Liu, Ming-Yueh; Lo, Cheng-Hsiang; Liao, Yi-Shu; Chao, Hsing-Lung; Lin, Kuen-Tze; Huang, Wen-Yen; Shen, Po-Chien; Tao, Chih-Cheng; Chen, Chang-Ming; Lin, Chun-Shu (Therapeutic Radiology and Oncology, 2018)
We present an atypical case of cutaneous head and neck squamous cell carcinoma (cHNSCC), with parotid gland metastasis. This 56-year-old female presented with a slowly enlarging mass at the left pre-auricular region over the past year. At first, the patient described that there was only a bulging mass without apparent skin lesion or skin defect and it grew slowly. A magnetic resonance imaging (MRI) demonstrated a large lobulated lesion measuring 51 mm × 55 mm × 56 mm within the left parotid gland, which had invaded the ipsilateral masseter muscle causing displacement of the left lateral pterygoid muscle. The diagnostic radiologist made a provisional diagnosis of mucoepidermoid carcinoma (MEC) based on the finding of MRI. The patient then received left total parotidectomy with ipsilateral supraomohyoid neck dissection. The diagnosis later revised to cHNSCC with parotid lymph node metastasis based on pathological findings. cHNSCC may present solely as parotid tumor without apparent skin lesion which might also mimic primary MEC of the parotid gland.